Angiotensin-converting Enzyme Inhibitor-mediated Angioedema Suspected of being Induced by Endobronchial Ultrasound-guided Transbronchial Needle Aspiration - Matsumoto, Kenji; Hayashi, Nobuyoshi (The Journal of the Japan Society for Respiratory Endoscopy, 2022)
Background. Angioedema can progress from edema of the tongue and lips to pharyngeal and laryngeal edema, resulting in life-threatening airway stenosis; therefore, appropriate treatment at the onset is important. Case. A 75-year-old male smoker receiving anticancer drug therapy for prostate cancer underwent endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) to examine the right lower paraventricular lymphadenopathy. No complications occurred within 24 h after the operation; however, angioedema developed after 48 h. The angiotensin-converting enzyme (ACE) inhibitor enalapril and dipeptidyl peptidase-4 (DPP-4) inhibitor linagliptin, which can exacerbate ACE inhibitor-mediated angioedema, were discontinued. Hydrocortisone succinate was infused; however, the patient's angioedema worsened. An emergency tracheostomy was performed. Thereafter, the air conduction stenosis due to edema was improved. Conclusion. We encountered a patient with prostate cancer who developed ACE inhibitor-mediated angioedema that may have been triggered by EBUS-TBNA. Angioedema due to ACE inhibitors rarely occurs; however, invasive procedures, such as EBUS-TBNA, may trigger the development of angioedema to ACE inhibitors if there are risk factors, such as smoking and DPP-4 inhibitor use.